2016
DOI: 10.6004/jnccn.2016.0135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Provincial-Wide Implementation of Screening for Distress on Healthcare Professionals' Confidence and Understanding of Person-Centered Care in Oncology

Abstract: Implementation of SFD was beneficial for HCPs' confidence and awareness of person-centeredness. Factors comprising different models of care, such as having site-based navigators and caring for single or multiple tumors, influenced outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…For example, in a study comparing patients who received care either before (n = 740) or after (n = 534) implementation of routine distress screening and appropriate interventions, patients in the post-implementation cohort showed significant improvements in psychological and physical symptoms as well as psychosocial wellbeing [21]. Follow-up analyses in this study assessed clinician confidence in managing distress and demonstrated significant improvements therein [22]. Similarly, in a large randomized controlled trial conducted by Basch et al, investigators found that patients who participated in weekly symptom monitoring via tablet computers actually had improved overall quality of life over time [23].…”
Section: Distress Is Measurable and Actionablementioning
confidence: 79%
“…For example, in a study comparing patients who received care either before (n = 740) or after (n = 534) implementation of routine distress screening and appropriate interventions, patients in the post-implementation cohort showed significant improvements in psychological and physical symptoms as well as psychosocial wellbeing [21]. Follow-up analyses in this study assessed clinician confidence in managing distress and demonstrated significant improvements therein [22]. Similarly, in a large randomized controlled trial conducted by Basch et al, investigators found that patients who participated in weekly symptom monitoring via tablet computers actually had improved overall quality of life over time [23].…”
Section: Distress Is Measurable and Actionablementioning
confidence: 79%
“…In addition, integrating emotion management into tobacco treatment could interplay with organization‐level characteristics. Tamagawa and colleagues 38 found that when distress screening was implemented, healthcare professionals reported greater confidence in managing distress; however, these results were observed only in cancer centers that had “site‐based navigators” (e.g., psychologists and social workers available for complex distress management). To avoid such unintended consequences, tobacco cessation treatment may need to consider program components that assess patients' willingness to participate in emotional management to support patient‐centered decision making, reduce patient burden, and support patients' desire to manage their emotional problems on their own 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Health care providers review the completed ppf with patients so as to understand which symptoms or concerns are most troublesome for the patient and to identify symptoms that require further clinical assessment and intervention. A process of shared decision-making with the patient is meant to follow, with the goal of identifying and putting into action the most meaningful clinical responses 20 . The health care provider then documents the patient's priority concern, clinical responses, and any referrals to other providers that have been initiated.…”
Section: Ppf Surveymentioning
confidence: 99%